Acquired Pediatric Blepharoptosis Related to Linear Scleroderma - Kao, Tina Y.; Yoon, Michael K.; Hwang, Thomas N.; Bloomer, Michele M.; McCulley, Timothy J. (Journal of pediatric ophthalmology and strabismus, 2011)
Periocular linear scleroderma coup de sabre has been seen in association with blepharoptosis. The authors describe a 4-year-old girl who developed left blepharoptosis simultaneously with a remote scalp lesion consistent with linear scleroderma coup de sabre. This case is unique in that the scalp lesion was distant from the affected eye.